CENP-H as a new prognostic biomarker for tumors: a real-world literature review - Li, Qiao; Tang, Yang; Zuo, Jie-Bin; Han, Hao; Tu, Guang-Xu; Chen, Cheng (Frontiers in Oncology, 2025)
Centromere protein H (CENP-H) is an important component of a functional centromere. Studies have demonstrated that CENP-H is overexpressed in renal cell, gastric, hypopharyngeal squamous cell, nasopharyngeal, endometrial, lung, cervical, esophageal, liver, colorectal, oral squamous cell, breast, and tongue carcinomas. CENP-H overexpression is positively correlated with a poor prognosis, pathological stage, T stage, and lymph node metastasis in patients with the above carcinomas. CENP-H can promote cancer growth and metastasis through PI3K/AKT, survivin, and mitochondrial apoptosis signaling mechanisms, and it can be regulated by long non-coding ribonucleic acid (lncRNA) plasmacytoma variant translocation 1 (PVT1)/miR-612, Sp1, or Sp3. This review aims to summarize the expression of CENP-H, the relationship between CENP-H expression and prognostic features, growth and metastasis of cancer in patients, as well as the mechanism of CENP-H in cancer. It also proposes a new candidate molecule for treating patients with cancer.